O romance de aventura europeu e a construção do outro: uma análise de O mundo perdido (1912), de Arthur Conan Doyle - Iwai, Marcia Miyuki (2010)
This monograph intends to investigate the genre adventure novel of the end of the 19th century and beginning of the 20th century, and the ways in which this genre builds the images of the Other. Considering that this Historical moment corresponds to the period of expansion of the European colonial empires, and of organization of the working class and feminist movements, the intension of this study is to make a reflection about the representations of workers, women, colonized peoples, and Nature in the adventure novels, as well as to think about the images of the Self, or of the heroes in these books men, Europeans, bourgeois, and colonizers. Starting with the analysis of the novel The Lost World, written in 1912 by Arthur Conan Doyle, we firstly studied the themes of the discovery of a new land, its exploitations, and the relations between the heroes and the inhabitants of this land. Secondly, we analyzed the weapons used by the heroes to conquer this land: Science, War, and Word. In a third moment, we made reflections about the images of the Feminine in the novel: the feminine identity of the land, the absence or the vilanization of the feminine characters, and the production and consumption of the adventure novel (which is usually described as a masculine genre) as the rejection of a so-called Feminine Literature. Finally, we studied the protagonists of the novel, or the virile heroes, and the world that they intend to build. Thus, from the analysis of The Lost World, which we regard as a model adventure novel, we made comparisons with other novels in the same genre, so that we could establish themes, rules, and conventions which can characterize the genre adventure novel